Esculin protects against methionine choline-deficient diet-induced non-alcoholic steatohepatitis by regulating the Sirt1/NF-B p65 pathway - Xi-Ding Yang; Zhuo Chen; Ling Ye; Jing Chen; Yong-Yu Yang (Taylor & Francis Group, 2021)
Context Esculin, an active coumarin compound, has been demonstrated to exert anti-inflammatory effects. However, its potential role in non-alcoholic steatohepatitis (NASH) remains unclear. Objective This study explored the hepatoprotective effect and the molecular mechanism of esculin in methionine choline-deficient (MCD) diet-induced NASH. Materials and methods Fifty C57BL/6J mice were divided into five groups: control, model, low dosage esculin (oral, 20 mg/kg), high dosage esculin (oral, 40 mg/kg), and silybin (oral, 105 mg/kg). All animals were fed a MCD diet, except those in the control group (control diet), for 6 weeks. Results Esculin (20 and 40 mg/kg) inhibited MCD diet-induced hepatic lipid content (triglyceride: 16.95 ± 0.67 and 14.85 ± 0.78 vs. 21.21 ± 1.13 mg/g; total cholesterol: 5.10 ± 0.34 and 4.08 ± 0.47 vs. 7.31 ± 0.58 mg/g), fibrosis, and inflammation (ALT: 379.61 ± 40.30 and 312.72 ± 21.45 vs. 559.51 ± 37.01 U/L; AST: 428.22 ± 34.29 and 328.23 ± 23.21 vs. 579.36 ± 31.93 U/L). In vitro, esculin reduced tumour necrosis factor-α, interleukin-6, fibronectin, and collagen 4A1 levels, but had no effect on lipid levels in HepG2 cells induced by free fatty acid. Esculin increased Sirt1 expression levels and decreased NF-κB acetylation levels in vivo and in vitro. Interfering with Sirt1 expression attenuated the beneficial effect of esculin on inflammatory and fibrotic factor production in HepG2 cells. Conclusions These findings demonstrate that esculin ameliorates MCD diet-induced NASH by regulating the Sirt1/ac-NF-κB signalling pathway. Esculin could thus be employed as a therapy for NASH.